Smart Plant Monitoring System Using Aquaponics Production Technological with Arduino Development Environment (IDE) and SMS Alert: A Prototype - Abu Bakar, Zahari; Muhammad Nor, Muhammad Zairil; Kadiran, Kamaru Adzha; Misnan, Mohamad Farid; Noorezam, Maisarah (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Aquaponics is one of the agricultural production technological advancements that should be publicized. Climate change, population expansion, water scarcity, soil degradation, and food security are just a few of the world’s most pressing issues. Aquaponics, which is a closed-loop system that combines hydroponics and aquaculture, may be able to deal with issues like climate change, population expansion, water scarcity, soil degradation, and food security. Thus, this paper aims to design and construct an aquaponics system that combines fish farming with plant growth. The system used a variety of sensors, including temperature and humidity sensors, ultrasonic sensors, and pH sensors, as well as microcontrollers like Arduino, to monitor and manage the water quality, plant humidity, and other variables. When the sensor identifies any abnormal circumstance, early warnings in the form of SMS and push notifications are immediately given to the user to ensure a healthy growing environment for fish and plants. The Arduino Development Environment (IDE) software is used to write a programme that connects the microcontroller to various sensors and other devices. pH sensors, temperature and humidity sensors, ultrasonic sensors, liquid crystal displays (LCDs), and GSM circuits are all built and connected to the system. A GSM notification message is sent to a mobile phone when the pH, temperature, and ultrasonic sensor findings are out of range. The data from this system’s monitoring reveals the values that have been taken on a daily basis. The graph demonstrated that the plant’s growth is increasing every day.